Learning Literature Using 4M Methods as an Effort to Increase Reading Interest of Elementary School - Kamila, Inneke Nurul; Sakti, Asri Wibawa (Indonesian Journal of Multidiciplinary Research, 2022)
Indonesia has implemented online learning in the past 2 years as an effort to minimize the transmission of the Covid-19 virus. The purpose of this study is to determine and measure reading literacy skills by providing treatment which is expected to increase reading interest in school students. The implementation of this community service program is expected to increase student interest in learning and be able to help facilitate teachers and parents in guiding and assisting children in online learning. Included in literacy learning using the 4M method as an effort to increase student interest in reading in elementary schools with inclusive education is carried out online. The method in this study uses quantitative methods. The results showed that there are still many elementary school students who do not know and understand literacy learning using the 4M method. Students' understanding of literacy learning using the 4M method can be improved by providing material through learning videos that can be accessed on YouTube provided by educators. The results showed that the average post-test score of students was 87.0% greater than the average pre-test score of 47.75% with a difference of 39.25%. Therefore, core competencies can increase students' interest in reading literacy.